ANALISIS KORELASI CITRA DATA PRIMER DENGAN DATA SEKUNDER MENGGUNAKAN CITRA GRID ANALYSIS AND DISPLAY SYSTEM (GrADS - Wahyu Jatmiko; Rahmat Gernowo (Youngster Physics Journal, 2014)
Indonesia has 13 (thirteen) the threat of catastrophic earthquakes, tsunamis, floods, landslides, volcanic eruptions, extreme waves and abrasion, extreme weather, drought, forest fires and land, buildings and residential fires, epidemics and disease outbreaks, failed technology, and social conflict. Research related to hydrometeorological predictable by doing a variety of approaches, one using remote sensing methods provided by the World Meteorological Organization (WMO) with the advantages of data is not affected by the location of the location such as the presence of a cliff, lake, or mountain.In the study image correlation analysis of primary data with secondary data using imagery Grid Analysis And Display System (Grads) have been analyzed the correlation between the image of the primary data with secondary data using Grid software image Analisys And Display System. The data used are rainfall, air temperature, and humidity, all of the data is the data on average monthly. Primary data were obtained from Badan Meteorologi, Klimatologi dan Geofisika (BMKG) Semarang and secondary data obtained by downloading from the National Oceanic And Atmospheric Administration (NOAA) website.The value of the correlation between the primary data with secondary data for rainfall data indicate a strong relationship , occurs when the amount of rainfall maximum correlation value is 0,67 and the value of correlation in the event the minimum rainfall is 0,79 . On air temperature data the value of the correlation time of maximum rainfall is 0.69 and the value of correlation in the event of rainfall minimum is -0,37 . Correlation values for air humidity data at the time of maximum precipitation is 0,01 and the magnitude of the correlation value at the time the minimum rainfall is 0,95 .Keywords : GrADS , disaster, correlation, extreme weather, dryness